Attachment within life history theory: an evolutionary perspective on individual differences in attachment. (February 2019) - Szepsenwol, Ohad; Simpson, Jeffry A
Highlights: The paper presents an integration of attachment theory and life history theory. Early-life harshness and/or unpredictability promotes insecure attachment. Adult attachment orientations, in turn, predict patterns of mating and parenting. Insecure attachment is linked to cognitive schemas suited for risky environments. Insecure attachment is linked to emotional profiles suited for risky environments. Abstract : In this article, we discuss theory and research on how individual differences in adult attachment mediate the adaptive calibration of reproductive strategies, cognitive schemas, and emotional expression and regulation. We first present an integration of attachment theory and life history theory. Then, we discuss how early harsh and/or unpredictable environments may promote insecure attachment by hampering parents' ability to provide sensitive and reliable care to their children. Finally, we discuss how, in the context of harsh and/or unpredictable environments, different types of insecure attachment (i.e. anxiety and avoidance) may promote evolutionary adaptive reproductive strategies, cognitive schemas, and emotional expression and regulation profiles.